Geriatric Gastroenterology - Pitchumoni, C. S.; Dharmarajan, T. (Springer New York : Imprint: Springer, 2012)
As aging trends in the United States and Europe in particular are strongly suggestive of increasingly older society, it would be prudent for health care providers to better prepare for such changes. By including physiology, disease, nutrition, pharmacology, pathology, radiology and other relevant associated topics, Geriatric Gastroenterology fills the void in the literature for a volume devoted specifically to gastrointestinal illness in the elderly. This unique volume includes provision of training for current and future generations of physicians to deal with the health problems of older adults. It will also serve as a comprehensive guide to practicing physicians for ease of reference. Relevant to the geriatric age group, the volume covers epidemiology, physiology of aging, gastrointestinal physiology, pharmacology, radiology, pathology, motility disorders, luminal disorders, hepato-biliary disease, systemic manifestations, neoplastic disorders, gastrointestinal bleeding, cancer and medication related interactions and adverse events, all extremely common in older adults; these are often hard to evaluate and judge, especially considering the complex aging physiology. All have become important components of modern medicine. Special emphasis is be given to nutrition and related disorders. Capsule endoscopy and its utility in the geriatric population is also covered. Presented in simple, easy to read style, the volume includes numerous tables, figures and key points enabling ease of understanding. Chapters on imaging and pathology are profusely illustrated. All chapters are written by specialists and include up to date scientific information. Geriatric Gastroenterology is of great utility to residents in internal medicine, fellows in gastroenterology and geriatric medicine as well as gastroenterologists, geriatricians and practicing physicians including primary care physicians caring for older adults.